2021
DOI: 10.15837/ijccc.2021.3.4186
|View full text |Cite
|
Sign up to set email alerts
|

Secure Real-Time Computational Intelligence System Against Malicious QR Code Links

Abstract: Web attackers aim to propagate malicious links using various techniques to deceive users. They attempt to control victims’ devices or obtain their passwords remotely, thereby acquiring access to bank accounts, financial transactions, or private and sensitive information they trade via the Internet. QR codes are accessible, free, easy to use, and can be scanned through several free apps on smartphones. As there is no standard structure or authentication phase in QR code generation, such codes are vulnerable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…One of the characteristics that are most frequently used for this filtering is genre [10]. This paper focused on a neural network based personalized music recommendation system that was created based on research on personalized music recommendation systems that solely use tag information [11] [12].…”
Section: Related Workmentioning
confidence: 99%
“…One of the characteristics that are most frequently used for this filtering is genre [10]. This paper focused on a neural network based personalized music recommendation system that was created based on research on personalized music recommendation systems that solely use tag information [11] [12].…”
Section: Related Workmentioning
confidence: 99%
“…The strength of each methodology, its weakness and general research gaps identified. According to [8] main objective is to detect malicious URLs embedded in QR codes. A dataset of 90 000 benign and malicious URLs was collected from various resources, and their lexical properties were extracted.…”
Section: Sql Injection Attackmentioning
confidence: 99%
“…Personal data can be associated with the QR codes on the patients' wristbands [15,16]. Healthcare services can use a QR code scanner application on their smartphone to access patient information, medication, and medical reports [17][18][19][20]. QR codes enable high-speed component scanning in factories [21].…”
Section: Introductionmentioning
confidence: 99%